An Unconventional Ligand for Scribble PDZ-4 Domain Mediates Its Interaction with Dusp26 - Raffaella Gallo; Erika De Sensi; Francesca Storino; Simona Panni (MDPI AG, 2022)
PDZ domains are involved in many cellular processes and are key regulators of the cell physiology. A huge number of studies have investigated the binding specificity of PDZ domains to the carboxyl-terminal sequence of target proteins, while the molecular mechanisms that mediate the recognition of internal binding regions are largely unexplored. In the present study, we describe a ligand motif located in the catalytic domain of the phosphatase Dusp26 which mediates its binding to the PDZ-4 of Scribble. Site-directed mutagenesis identified a conserved tyrosine residue as relevant for the binding. The interaction with the PDZ domain could help the phosphatase to recruit its specific targets.